Microfiber-based sensor for measuring uric acid concentrations - Saidin, Norazlina; Idris, N. F.; Amaluddin, M. N.; Irawati, Ninik; Md Ralib, Aliza Aini; Harun, Sulaiman Wadi (Universiti Teknikal Malaysia Melaka, 2018)
Microfiber sensor is proposed and demonstrated using a fiber optic displacement sensor (FODS) based on intensity modulation technique for measurement of different concentrations of uric acid. The proposed sensor uses singlemode fiber (SMF) tapered using flame brushing technique to enhance the evanescent field around the fiber core to interact with the uric acid. The tapered area is bent manually and sets vertically on a clamp, facing the mirror in the beaker. It is placed within the linear range of a sensor’s displacement curve of 0 to 5000 µm. The calibration of tapered fiber sensor was done both in the air and diluted water. The sensor is capable of measuring the concentrations of uric acid from 100 ppm to 500 ppm with a measured sensitivity of 0.0218 dBm/ppm. The linearity and resolution of the proposed sensor are 99.21% and 28.219 ppm, respectively. In addition, the proposed microfiber FODS sensor using SMF exhibit good stability and repeatability. It provides numerous advantages in terms of simple design, less production cost and operation without forfeiting its sensitivity.